ENGLISH FOR SPECIFIC PURPOSES FOR NURSING STUDENTS’ BASED ON NEED ANALYSIS - Mansur, Musdalifah; Syaripuddin, Anci Bte (Fakultas Keguruan dan Ilmu Pendidikan, 2017)
The present study was aimed to find out the topics of English for Specific Purposes (ESP) for Nursing students of Islamic State University of Alauddin Makassar (UINAM), Indonesia, based on need analysis.  This research employed a qualitative research. The participants were 50 nursing students, 5 graduates and 3 English lecturers who teach more than two years in this university. For collecting data, the students and graduates were required to fill out the questionnaires, and a semi-structured interview was applied by the researcher for the English lecturers. The research result indicates that 14 topics of English materials which related to the students major. Speaking as the most difficult language skill was needed by the students. It was followed by writing, reading, and listening. In line with teaching method, the students need practical demonstration as teaching method should apply in the classroom. The result of this research as the topic of ESP will be proposed to the institution, curriculum designer, and lecturer in order to design English Material for nursing students based on need analysis.